Childhood leukaemia risk and residential proximity to busy roads. (December 2018) - Tamayo-Uria, Ibon; Boldo, Elena; García-Pérez, Javier; Gómez-Barroso, Diana; Romaguera, Elena Pardo; Cirach, Marta; Ramis, Rebeca
Abstract: Background: Current evidence suggests that childhood leukaemia can be associated with residential traffic exposure; nevertheless, more results are needed to support this conclusion. Objectives: To ascertain the possible effects of residential proximity to road traffic on childhood leukaemia, taking into account traffic density, road proximity and the type of leukaemia (acute lymphoid leukaemia or acute myeloid leukaemia). Methods: We conducted a population-based case-control study of childhood leukaemia in Spain, covering the period 1990–2011. It included 1061 incidence cases gathered from the Spanish National Childhood Cancer Registry and those Autonomous Regions with 100% coverage, and 6447 controls, individually matched by year of birth, sex and autonomous region of residence. Distances were computed from the respective participant's residential locations to the different types of roads and four different buffers. Using logistic regression, odds ratios (ORs) and 95% confidence intervals (95%CIs), were calculated for four different categories of distance to roads. Results: Cases of childhood leukaemia had more than three-fold increased odds of living at <50 m of the busiest motorways compared to controls (OR = 2.90; 95%CI = 1.30–6.49). The estimates for acute lymphoid leukaemia (ALL) were slightly higher (OR = 2.95; 95%CI = 1.22–7.14), while estimates for cases with the same address at birth and at diagnosis were lower (OR = 2.40; 95%CI = 0.70–8.30). Conclusions: Our study agrees with the literature and furnishes some evidence that living near a busy motorway could be a risk factor for childhood leukaemia. Highlights: Association between residing close to a busy major road and risk for childhood leukaemia. Leukaemia cases had a higher odds of exposure to motorways compared to controls. Leukemia cases had a higher odds of exposure to higher traffic density compared to controls.